Spectrophotometric Determination of Copper(II) in Sugarcane Spirit Using 1-(2-pyridylazo)-2-naphthol and a Homogeneous Ternary Mixture of the Solvents Water, Ethanol and Methyl Isobutyl Ketone - Souza, J. C. [UNESP]; Toci, A. T.; Beluomini, M. A. [UNESP]; Eiras, S. P. (Brazilian Chemical Soc, 2016)
A fast, inexpensive and sensitive new analytical technique is described for the spectrophotometric determination of copper(II) ions in sugarcane spirit, employing the complexation agent 1-(2-pyridylazo)-2-naphthol (PAN). Homogeneous ternary solvent systems, commonly known as single-phase solutions, can be used as a way of preconcentrating samples. Here, a solvent mixture consisting of water-ethanol-methyl isobutyl ketone (MIBK) at a ratio of 5.0: 5.0: 2.5 (v/v) was employed. Maximum formation of the bis[1-(2-pyridylazo)-2-naphthalate] copper(II) (Cu(PAN)(2)) complex was achieved with 0.01% (m/v) of PAN in MIBK, pH 4.5 in the aqueous fraction, 15 min reaction time, and temperature of 20 degrees C. It was found that iron(III) and nickel(II) ions interfered in the reaction. Malonic acid at a concentration of 0.10% (m/v) was therefore used as a masking agent, which reduced the magnitude of the interference effect from around 10.4% to approximately 2.6%. Under optimized conditions for determination of copper(II), the analytical curve obtained could be described by: Delta Abs = 0.152 C-Cu(II) + 0.011 (r(2) = 0.9997). Linearity was obtained up to a concentration of 8.0 mg L-1 of copper(II), and limits of detection and quantification (calculated using the standard deviation of the blank) were 0.02 and 0.13 mg L-1 of copper(II), respectively, in the aqueous fraction of the single-phase solution. The method was applied to determine copper(II) ions in commercial brands of sugarcane spirits. The results obtained by the proposed method were statistically similar with those given by the standard method.
Keywords: Copper; molecular absorption spectrophotometry; 1-(2-pyridylazo)-2-naphthol; homogeneous ternary solvent system; sugarcane spirit